2002
DOI: 10.1124/mol.62.2.210
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+Channel Antagonists Mibefradil and Pimozide Inhibit Cell Growth via Different Cytotoxic Mechanisms

Abstract: We show that mitogenic cells expressing T-type Ca 2ϩ channels (T-channels) are more sensitive to the antiproliferative effects of the drugs pimozide and mibefradil than cells without significant T-channel expression. The growth of Y79 and WERI-Rb1 retinoblastoma cells, as well as MCF7 breast cancer epithelial cells, all of which express T-channel current and mRNA for T-channel subunits, is inhibited by pimozide and mibefradil with IC 50 values between 0.6 and 1.5 M. Proliferation of glioma C6 cells, which show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 34 publications
2
77
0
Order By: Relevance
“…In relation to I Ca , our findings demonstrate that melatonin treatment was able to reduce both T-and L-type Ca 2 þ current amplitude and to provoke an alteration of the current voltage dependence along with a decrease of intracellular Ca 2 þ concentration. Since Ca 2 þ seems to be a crucial regulator of the cell cycle necessary for proper proliferation (Bertolesi et al, 2002;Gray et al, 2004;Naziroğlu et al, 2012;Wang et al, 2000), the associated reduction of free [Ca 2 þ ] i observed in our experiments supports the clue that melatonin may contribute to the decline of proliferation also disturbing internal Ca 2 þ homeostasis. The G-protein-coupled melatonin MT1 receptors are expressed in MCF-7 cells (Girgert et al, 2009;Hill et al, 2011b;Jablonska et al, 2013;Jawed et al, 2007;Rich et al, 1999) and, via the inhibition of adenylate cyclase activity (Jablonska et al, 2013;Jawed et al, 2007), their activation leads to the decrease of adenosine 3 0 , 5 0 -cyclic monophosphate (cAMP) synthesis.…”
Section: Ctrsupporting
confidence: 72%
See 2 more Smart Citations
“…In relation to I Ca , our findings demonstrate that melatonin treatment was able to reduce both T-and L-type Ca 2 þ current amplitude and to provoke an alteration of the current voltage dependence along with a decrease of intracellular Ca 2 þ concentration. Since Ca 2 þ seems to be a crucial regulator of the cell cycle necessary for proper proliferation (Bertolesi et al, 2002;Gray et al, 2004;Naziroğlu et al, 2012;Wang et al, 2000), the associated reduction of free [Ca 2 þ ] i observed in our experiments supports the clue that melatonin may contribute to the decline of proliferation also disturbing internal Ca 2 þ homeostasis. The G-protein-coupled melatonin MT1 receptors are expressed in MCF-7 cells (Girgert et al, 2009;Hill et al, 2011b;Jablonska et al, 2013;Jawed et al, 2007;Rich et al, 1999) and, via the inhibition of adenylate cyclase activity (Jablonska et al, 2013;Jawed et al, 2007), their activation leads to the decrease of adenosine 3 0 , 5 0 -cyclic monophosphate (cAMP) synthesis.…”
Section: Ctrsupporting
confidence: 72%
“…Since several studies demonstrated that human mammary cancer cell lines express voltage-dependent Ca 2 þ channels (Bertolesi et al, 2002;Ohkubo and Yamazaki, 2012), we intended to evaluate the effects of melatonin on voltage-dependent Ca 2 þ currents in MCF-7 cells cultured in growth medium. In control conditions we could observe a low voltage-activated inward transient current starting from À 60 mV up to À 40 mV.…”
Section: Melatonin Reduces Ca 2 þ Currents In Mcf-7 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voltage gated Ca 2þ channels facilitate transient Ca 2þ influx from the environment into the cytoplasm and appear mostly in excitable tissues, but also are unusually expressed in cancer cells. Low-voltage activated Ca 2þ channels, termed T-type Ca 2þ channels, recently gained attention in cancer therapy, because their inhibition decreased proliferation of glioblastoma cells (3,4), breast adenocarcinoma cells (5,6), melanoma cells (7), and esophageal carcinoma cells (8). In addition, an antagonist selective for T-type Ca 2þ channels, mibefradil, has been proposed recently as a sensitizing agent with activity in vivo in combination with chemo-(9) or radiotherapy (10).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, T-type channel blockers such as mibefradil and pimozide, which cannot distinguish between Ca v 3.1 and Ca v 3.2 channels, were used to investigate the regulation of cancer cell proliferation (13)(14)(15)(16)(17). Since there is a possibility that these isoforms exhibit different functions in tumors, if both isoforms are inhibited by such drugs to the same extent, the results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%